Developing a roadmapping system for knowledge management in an organisation - Yee, Choy Leong; Teoh, Kenny Guan Cheng (Universiti Putra Malaysia Press, 2015)
This study aims to develop a roadmapping system that can be used as a knowledge management tool for any organization. The study employed a structured action research to test the implementation of the proposed roadmapping system in a real industrial environment. An internal facilitator collected data through a clinical inquiry approach. The output is a roadmapping system for knowledge management for an organisation, which enhances strategic capability. It also helps to capture and handle the complexities of business strategies in a simple way or that is easy to understand. The proposed roadmapping system was only tested on one firm. Pending further research, these findings should not be generalised. The proposed roadmapping system improves the capability of an organisation to plan and implement its strategies. The proposed system can be used for strategic planning and knowledge management - it allows managers to "kill two birds with one stone." Unlike conventional technology roadmapping (TRM) research that focuses more on the hard aspects of technical and economic elements, this study explores the soft aspects of knowledge management for improving the strategic capability of an organisation. This research has extended the traditional boundary of TRM to include effective information systems.